A revision of the descriptions of ectomycorrhizas published since 1961 - De Roman, Miriam; Clavería, Vanessa; Maria De Miguel, Ana (Mycological Research, 2005)
All available publications providing descriptions of ectomycorrhizas (ECM) were reviewed in order to build a database containing details on fungus forming the ECM, host tree, country where the material for description was collected, and habitat of the ECM. Other secondary data were also recorded. In all 1244 descriptions of ECM published since 1961 in 479 papers were reviewed. The number of diﬀerent ECM morphotypes described was 814. Most ECM described were collected in Europe and North America. Gymnosperms were the most common tree associates, and boreal and temperate forests the most studied ecosystems. Fungal symbionts were mostly Basidiomycota, epigeous, and with mushroom-like morphology. The paper also addresses the gaps in ECM knowledge that mycorrhizologists should address in future studies.
Keywords: descriptions; Ectomycorrhizae; habitat (PG); host tree